Analysis of proactive, static and dynamic unipedal balance in young gymnasts during adolescence - Gómez-Landero, L. A.; Leal del Ojo, P.; Floria, P. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aims of this study were to evaluate the effect of age in young acrobatic gymnasts on performance and asymmetry between lower limbs in proactive, static, and dynamic balance. 37 acrobatic gymnasts (31 females and 6 males) were divided in Early (EA, n=10), Middle (MA, n=16), and Late (EL, n=11) adolescence according to peak height velocity. Three types of unipedal balance tests were applied and normalised relative to participants height: Y-Balance Test, single leg stance test (centre of pressure measurements with a force platform), time to stabilization after single leg landing test. EA gymnasts had worse static balance compared to MA and LA, and showed greater asymmetry in proactive balance between both legs compared to MA. These results must be considered given the high demands of static and proactive balance in early adolescence acrobatic gymnasts.